Aspectos quali-quantitativos da arborização urbana da Área Norte do campus da UFSCar, São Carlos (SP) - Lessi, Bruno Flório (2014)
The urban trees plays an important role in providing a wide range of economic, ecological and social benefits. This study was carried out to analyze the urban trees of the North area of the Federal University of São Carlos campus by performing a tree inventory to assist in planning and management of this. The survey was conducted based on the General UFSCar Map - Campus San Carlo (2013), which used a random sampling for the individual analysis of each individual component of urban trees. The survey consisted information as the name of the species, origin, conflicts, physical damage, size, planting, phytosanity, integrity and functionality. As a result, we found 4193 individuals composing the afforestation of North campus area, where they were identified to species level in 2548 individuals, the community consists of 130 species belonging to 107 genera and 46 families, among species, 52 were as local native, native 13 from other regions of Brazil and 65 exotic to Brazil. For technical analysis were sampled 1422 individuals. 18.9% of individuals were found presenting conflicts with urban infrastructure and 53.7% with physical injury by pruning. The urban trees is mostly with good physical integrity, with low numbers of risks and fitossanidades. The mapping was an issue for space indication of individuals enabling an analysis of its composition and distribution. Also reveals the need for planning for better conflict management and management of trees, which can be started with the information generated in this work.